Hypoglycemic Effect of Mahogany (Swietenia macrophylla King) Bark Extracts in Alloxan-induced Diabetic Rats - Syamsul Falah; Mega Safithri; Takeshi Katayama; Toshisada Suzuki (Wood Research Journal, 2010)
In this study, in vivo hypoglycemic activity of mahogany (Swietenia macrophylla) bark extracts was evaluated against alloxan-induced diabetic rats. The hypoglycemic effect was compared to that of standard glibenclamide. Oral administration of hot water and methanol extracts at a dose of 250 mg/kg body weight for thirteen days of daily treatment to diabetic rats was found to possess significant dose dependant hypoglycemic effect in diabetic rats. It less active than that of glibenclamide at dose of 3.22 mg/kg. However, the hot water extract showed significant hypoglycemic activity compared to that standard drug.  Phytochemical analysis of hot water and methanol extracts has shown posistive  test for the presence of  alkaloids, flavonoids, tannins, saponins, dan terpenoids. Histopathological studies of pancreas revealed its significant effect of β-cell count. Therefore, the hot water extract could serve as good adjuvant to other oral hypoglycemic agents and seems to be promising for the development of phytomedicines for diabetes mellitus.